Correlation between Selective Motor Control of the Lower Extremities and Balance in Spastic Hemiplegic Cerebral Palsy: a randomized controlled trial - Amira H. Mohammed; Hager R. El-Serougy; Amel E Abdel Karim; Mohamad Sakr; Samah M. Sheha (BMC, 2023)
Abstract Background Children with cerebral palsy (CP) have motor deficits caused by spasticity, weakness, contractures, diminished selective motor control (SMC), and poor balance. The purpose of the current study was to evaluate the influence of mirror feedback on lower extremity selective motor control and balance in children with hemiplegic cerebral palsy. Understanding the relationship between SMC and balance will help children with hemiplegic CP receive more appropriate therapies. Methods Forty-seven children of both sexes diagnosed with hemiplegic CP participated in the study. Group1 (Gr1 - control group) received conventional physical therapy training while group 2 (Gr2 - intervention group) received conventional physical therapy training in addition to bilateral lower extremity mirror therapy (MT). The primary outcome measure used was Selective Control Assessment of Lower Extremity scale (SCALE), while the secondary outcome measure was the Pediatric Balance Scale (PBS). Results There were significant differences in Selective Control Assessment of Lower Extremity Scale (SCALE) and Pediatric Balance Scale (PBS) between both groups in favor of Gr2. After treatment, both groups improved significantly, yet Gr2 outperformed Gr1 by a large margin. Conclusion Mirror therapy may be a useful addition to home-based motor interventions for children with hemiplegic CP due to its relative simplicity, low cost, and high patient adherence. Additionally, it may help children improve their selective motor skills and balance. Trial registration Current Controlled Trials using African Clinical Trials Registry website with ID number PACTR202105604636415 retrospectively registered on 21/01/202.